2022
DOI: 10.1155/2022/6362344
|View full text |Cite
|
Sign up to set email alerts
|

Classic Signaling Pathways in Alveolar Injury and Repair Involved in Sepsis-Induced ALI/ARDS: New Research Progress and Prospect

Abstract: Sepsis is a common critical clinical disease with high mortality that can cause approximately 10 million deaths worldwide each year. Acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) is a common clinical complication of sepsis, which occurs primarily as diffuse alveolar injury, hypoxemia, and respiratory distress. The mortality rate of ALI/ARDS is as high as 30%-40%, which greatly endangers human health. Due to the unclear pathogenesis of ALI/ARDS, its treatment is still a worldwide problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 99 publications
(85 reference statements)
1
36
0
Order By: Relevance
“…Acute respiratory distress syndrome (ARDS) is a serious respiratory disease secondary to trauma, shock, infection and other non-cardiogenic diseases. ARDS is one of the most common and serious complications in the development of sepsis ( 11 ). The mortality rate of ARDS is as high as 30%-40% ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acute respiratory distress syndrome (ARDS) is a serious respiratory disease secondary to trauma, shock, infection and other non-cardiogenic diseases. ARDS is one of the most common and serious complications in the development of sepsis ( 11 ). The mortality rate of ARDS is as high as 30%-40% ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Release of antiviral pro-inflammatory immune response molecules into the systemic circulation can result in sepsis and can lead to ARDS ( 166 ). In animal models of post-viral ARDS, murine GM-CSF demonstrated immunomodulatory effects that improved the clinical response and symptoms associated with viral respiratory infections ( 167 , 168 ).…”
Section: Immune Responses To Infections and Risk Of Gm-csf Insufficiencymentioning
confidence: 99%
“…Previous studies have shown that PANoptosis was closely related to lung injury. 3,15 During severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, patients develop systemic symptoms of varying severity and induce PANoptosis, leading to further exacerbation of the pulmonary cytokine storm, and COVID-19associated pneumonia can progress to ARDS. 5,16,17 Because of the complexity of PANoptosis, the treatment maybe fails if three PCDs in PANoptosis cannot be simultaneously inhibited to prevent the compensatory activation of other pathways.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Acute lung injury (ALI) is one of the most common and intractable critical diseases with high mortality, and it has recently been rediagnosed as mild or moderate acute respiratory distress syndrome (ARDS). , A major cause of ALI/ARDS is sepsis, and there are nearly 50 million cases of sepsis and 11 million sepsis-related deaths worldwide per year. , A recent global survey reported that the mortality from coronavirus disease 2019 (COVID-19) has soared to 45% because more than 30% of patients has complications from ARDS . Currently, the treatment of ALI/ARDS is mainly supportive such as oxygen therapy, noninvasive mechanical ventilation, and other respiratory support treatments, and there is no specific treatment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation